2009
DOI: 10.3155/1047-3289.59.6.733
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Personal Exposures to Ambient Air Toxics in Camden, New Jersey: An Evaluation Study

Abstract: This study presents the Individual Based Exposure Modeling (IBEM) application of MENTOR (Modeling ENvironment for TOtal Risk studies) in a hot spot area, where there are concentrated local sources on the scale of tens to hundreds of meters, and an urban reference area in Camden, NJ, to characterize the ambient concentrations and personal exposures to benzene and toluene from local ambient sources. The emission-based ambient concentrations in the two neighborhoods were first estimated through atmospheric disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Evaluations of the performance of AERMOD relative to other air dispersion estimation techniques indicted that AERMOD provides location-specific exposure risk estimates with higher accuracy, simulates pollutant dispersion at or under 50 km accurately, and tends to generate lower concentration estimates for point sources at the point of maximum air concentration. [21][22][23] The Communities Actively Researching Exposure Study (CARES) in Marietta, OH provided an opportunity to gain a greater understanding of the link between concentrations of ambient air Mn and children's exposure. 24 Marietta is home to the longest operating ferromanganese refinery in the nation, Eramet Marietta Incorporated (EMI).…”
Section: Stationary Air Samplingmentioning
confidence: 99%
“…Evaluations of the performance of AERMOD relative to other air dispersion estimation techniques indicted that AERMOD provides location-specific exposure risk estimates with higher accuracy, simulates pollutant dispersion at or under 50 km accurately, and tends to generate lower concentration estimates for point sources at the point of maximum air concentration. [21][22][23] The Communities Actively Researching Exposure Study (CARES) in Marietta, OH provided an opportunity to gain a greater understanding of the link between concentrations of ambient air Mn and children's exposure. 24 Marietta is home to the longest operating ferromanganese refinery in the nation, Eramet Marietta Incorporated (EMI).…”
Section: Stationary Air Samplingmentioning
confidence: 99%
“…At state and local levels, Lupo and Symanski [34] found 1996 NATA underestimated 8 out 15 HAPs and 1999 NATA underestimated 18 out of 27 HAPs in Texas. Wang et al [50] found general agreement for benzene and toluene concentrations modeled by 1999 NATA in Camden, New Jersey. Logue et al [33] reported that the 2002 NATA underestimated 32 out of 49 HAPs measured at 7 sites in and around Pittsburgh, Pennsylvania.…”
Section: Discussionmentioning
confidence: 99%
“…It was notable that previous studies found good agreement for benzene; however, our results showed moderate agreement, possibly due to different comparison methods. These findings indicate that model-to-monitor agreement was inconsistent by region and chemical, and under-prediction was more frequent [35,36,50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations